Financial intermediation in an overlapping generations model with transaction costs - Hasman, Augusto; Samartín, Margarita; van Bommel, Jos (Journal of economic dynamics & control, 2014)
We analyze an overlapping generations economy where agents interact to share liquidity risk. We show that a pure exchange economy has excessive trade in equilibrium because agents interact to rebalance their portfolios. Intergenerational financial intermediaries reduce the number of interactions because agents only transact when they face liquidity needs. In the absence of asset risk, intermediaries match redemptions with deposits and dividends, and never sell assets. If the economy is subject to transaction costs, the intermediated economy can sustain higher stationary investment and welfare. We also find that dead weight transaction costs can increase welfare because it protects banks from interbank arbitrage and dampens the inherent cyclicality of market economies.